2013
DOI: 10.1007/s00520-012-1688-0
|View full text |Cite
|
Sign up to set email alerts
|

A literature synthesis of symptom prevalence and severity in persons receiving active cancer treatment

Abstract: Purpose Patients with cancer experience acute and chronic symptoms caused by their underlying disease or by the treatment. While numerous studies have examined the impact of various treatments on symptoms experienced by cancer patients, there are inconsistencies regarding the symptoms measured and reported in treatment trials. This article presents a systematic review of the research literature of the prevalence and severity of symptoms in patients undergoing cancer treatment. Methods A systematic search for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
214
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 271 publications
(233 citation statements)
references
References 56 publications
8
214
1
2
Order By: Relevance
“…This was at odds with the literature and findings such as by Sun et al (2005) who reported nausea and vomiting to be significantly distressing symptoms amongst patients undergoing chemotherapy for ovarian carcinoma. One reason for this can be attributed to the advent and usage of effective new antiemetic drugs, the efficacy of which can be seen in the far fewer reports of vomiting but with much less progress in the management of nausea (Reilly et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This was at odds with the literature and findings such as by Sun et al (2005) who reported nausea and vomiting to be significantly distressing symptoms amongst patients undergoing chemotherapy for ovarian carcinoma. One reason for this can be attributed to the advent and usage of effective new antiemetic drugs, the efficacy of which can be seen in the far fewer reports of vomiting but with much less progress in the management of nausea (Reilly et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In a review of 21 multinational studies which included a total of 4067 cancer patients across 11 different cancer types, Reilly et al summarized the prevalence and severity of common symptoms. Fatigue was most prevalent, reported by up to two-thirds of patients during or after treatment [7]. Pain, sleep disturbance, weight loss, and anorexia/appetite changes were reported by over 40% of cancer survivors [7].…”
Section: Validated General Cancer Patient-reported Outcomes Instrumentsmentioning
confidence: 99%
“…Fatigue was most prevalent, reported by up to two-thirds of patients during or after treatment [7]. Pain, sleep disturbance, weight loss, and anorexia/appetite changes were reported by over 40% of cancer survivors [7]. Additional common symptoms were gastrointestinal (constipation, diarrhea, nausea and vomiting) (15-40%), respiratory (dyspnea, cough) (44-52%), numbness/tingling (40%), sexual dysfunction (37%), dizziness (27%), hair loss (21%) and cognitive dysfunction (44%).…”
Section: Validated General Cancer Patient-reported Outcomes Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The symptoms are prevalent and severe in patients with cancer. Any clinical study to evaluate the impact of treatment should consider the assessment of symptoms, mainly in patients at advanced stages of disease (21) .…”
Section: Dicussionmentioning
confidence: 99%